Accrual practices and reform experiences in OECD countries Results of the 2016 OECD Accruals Survey - Moretti, Delphine (OECD Publishing, 2016)
Over the past two decades, a growing number of governments have begun moving away from pure cash accounting toward accrual accounting. In the wake of these reforms, the budget presentation, audit techniques, and accounting standards setting and consolidation practices have evolved significantly. This paper reviews the current accrual practices in OECD countries, challenges associated with accruals reforms, and assesses the benefits achieved. It finally considers initiatives in OECD countries to make better use of accrual information in the future. JEL Classification: H60, H83 Keywords: accrual accounting, accrual budgeting, accounting practices, budgeting practices, consolidation, external audit, accounting standard setting
Keywords: Finance and Investment; Governance